Oriel College - possibly Holt, Thomas
Perhaps the most revealing of examples from this period is this elevation of Oriel College, Oxford, in which the early building of 1326 has been embellished by Tudor, Dutch, Flemish, and classical details. This was possibly, the work of Thomas Holth (ca. 1578-1624) who was active as an architect at this time and who was know to have made a complete study of Italian buildings.